2010
DOI: 10.1128/iai.00590-09
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Negatively Regulates Hemolysin Transcriptionally and Posttranslationally in Vibrio cholerae

Abstract: Recent work has shown that in addition to cholera toxin (CT) and the toxin-coregulated pilus (TCP), other cytotoxic proteins in Vibrio cholerae also cause disease symptoms, and this is particularly evident in strains lacking CT. One such protein is the hemolysin encoded by hlyA. Here we show that, like CT and TCP, HlyA is repressed by the quorum-sensing-regulated transcription factor HapR. This repression occurs on two levels: one at the transcriptional level that is independent of the metalloprotease HapA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 50 publications
(46 reference statements)
0
49
0
Order By: Relevance
“…It is interesting to note that the predominant role of Dly in the lysis of mouse and turbot erythrocytes prevents us from observing whether this repression also occurs in these two blood types. Recently, it was reported that V. cholerae HlyA hemolysin is negatively regulated via the quorum-sensing-regulated transcription factor HapR, and this negative regulation is exerted at the transcriptional and posttranslational levels (45). We demonstrated, using transcriptional lacZ fusions, that inhibition of HlyA pl in P. damselae subsp.…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that the predominant role of Dly in the lysis of mouse and turbot erythrocytes prevents us from observing whether this repression also occurs in these two blood types. Recently, it was reported that V. cholerae HlyA hemolysin is negatively regulated via the quorum-sensing-regulated transcription factor HapR, and this negative regulation is exerted at the transcriptional and posttranslational levels (45). We demonstrated, using transcriptional lacZ fusions, that inhibition of HlyA pl in P. damselae subsp.…”
Section: Discussionmentioning
confidence: 97%
“…Many virulence factors, including cholera toxin, the toxin-coregulated pilus, and the HlyA hemolysin are expressed at a low cell density and then repressed at a high cell density by HapR. However, HapR also positively regulates the expression of other virulence genes, such as the HA/protease and a T6SS, and represses the extracellular polysaccharide locus and biofilm development (29,34,61,(76)(77)(78). The nature of the genes regulated by the central output regulator of the quorum pathway has been examined for a few other Vibrio species.…”
Section: Discussionmentioning
confidence: 99%
“…There are additional two genes predicted to encode hemolysin-like proteins; however, deletion of these two genes did not affect the hemolytic activity of V. fluvialis (data not shown). In V. cholerae, QS negatively regulates hemolysin gene expression (41). To test whether QS controls hemolysin expression in V. fluvialis, we examined vfh expression in the wild type and QS mutants using qRT-PCR (Fig.…”
Section: Fig 4 Hapr Regulation Of Ahl-vfqr (A) Effect Of Hapr Deletimentioning
confidence: 99%